2023
DOI: 10.1039/d3ce00730h
|View full text |Cite
|
Sign up to set email alerts
|

Study on the optical properties and electronic structures of Ba-doped KH2PO4 crystals

Hao Hu,
Wei Hong,
Tingyu Liu
et al.

Abstract: Potassium dihydrogen phosphate (KDP) is widely used in electro-optical switches and inverter crystals in Inertial confinement fusion (ICF). Ba substitute for K ( BaK )was found to be one of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Sn 3 O 2 (OH)(HSO 4 ) notably exhibits significantly higher birefringence compared to Sn 2 OSO 4 . Moreover, the birefringence of Sn 3 O 2 (OH)(HSO 4 ) not only surpasses that of some reported traditional alkali metal and alkaline earth metal sulfate and phosphate crystals such as Li 5 Cs(SO 4 ) 3 (0.018@1064 nm), Li 2 SO 4 ·H 2 O (0.023@1064 nm), Rb 2 Mg(SO 4 ) 4 (0.0175@534 nm), KH 2 PO 4 (0.034@1064 nm), LiCs 2 PO 4 (0.008@1064 nm), but also compares favorably to certain sulfate and phosphate crystals equipped with other functional building blocks, such as Sn 2 PO 4 F (0.126@546 nm) . Sb 6 O 7 (SO 4 ) 2 (0.052@1064 nm), Hg 3 O 2 SO 4 (0.10@546 nm), K 4 Sb(SO 4 ) 3 Cl (0.066@546 nm), CsSbF 2 SO 4 (0.112@1064 nm), RbSbSO 4 F 2 (0.10@1064 nm), Na 3 Sc 2 (PO 4 ) 2 F 3 (0.063@1064 nm) .…”
Section: Resultsmentioning
confidence: 78%
“…Sn 3 O 2 (OH)(HSO 4 ) notably exhibits significantly higher birefringence compared to Sn 2 OSO 4 . Moreover, the birefringence of Sn 3 O 2 (OH)(HSO 4 ) not only surpasses that of some reported traditional alkali metal and alkaline earth metal sulfate and phosphate crystals such as Li 5 Cs(SO 4 ) 3 (0.018@1064 nm), Li 2 SO 4 ·H 2 O (0.023@1064 nm), Rb 2 Mg(SO 4 ) 4 (0.0175@534 nm), KH 2 PO 4 (0.034@1064 nm), LiCs 2 PO 4 (0.008@1064 nm), but also compares favorably to certain sulfate and phosphate crystals equipped with other functional building blocks, such as Sn 2 PO 4 F (0.126@546 nm) . Sb 6 O 7 (SO 4 ) 2 (0.052@1064 nm), Hg 3 O 2 SO 4 (0.10@546 nm), K 4 Sb(SO 4 ) 3 Cl (0.066@546 nm), CsSbF 2 SO 4 (0.112@1064 nm), RbSbSO 4 F 2 (0.10@1064 nm), Na 3 Sc 2 (PO 4 ) 2 F 3 (0.063@1064 nm) .…”
Section: Resultsmentioning
confidence: 78%
“…18 A large lattice distortion (9.26–22.33%) in H–O bonds induced by Ba K defects was found in paraelectric phase KDP crystals. 19 The linear absorption spectra indicate that the presence of Al 3+ ions minimally impacts the linear absorption of the KDP crystals. 20 The influence of the Zn 2+ ion and its cluster defects on the KDP crystals was also studied by DFT, and it is found that with increasing Zn 2+ concentration, the crystal structure becomes unstable, which will affect the optical properties.…”
Section: Introductionmentioning
confidence: 95%